Catalytic Approaches for CO2 Conversion to Value‐Added Products: An Overview of Life Cycle Assessment Studies - Anastasia Pappa; Cuong Pham‐Huu; Spiros Papaefthimiou; Spyridon Zafeiratos (Advanced Energy & Sustainability Research)
The urgent need to address climate change has driven efforts to develop sustainable strategies for environmental mitigation. Among these, the catalytic and electrocatalytic conversion of CO2 into value‐added products using renewable energy holds significant promise. E‐fuels, produced through heterogeneous catalytic processes involving CO2 and renewable hydrogen, exemplify this potential, offering sustainable alternatives. Life cycle assessment (LCA) is a critical tool to evaluate the environmental impacts of CO2 utilization technologies, providing a comprehensive analysis of a broader sustainability metrics. This review synthesizes findings from selected LCA studies, focusing on the environmental impacts of CO2 conversion processes, particularly those utilizing heterogeneous catalysis and electrochemical reduction. The goal is to provide practical insights and recommendations to help technology developers identify pathways with the lowest environmental impact and optimize sustainable CO2 utilization technologies. It is highlighted that despite the widely recognized advantages of CO2‐based processes, the environmental benefits cannot be guaranteed, while the carbon intensity of the electricity source used significantly affects the outcomes. The review identifies possible improvement strategies associated with electricity sources, CO2 capture methods, catalytic processes, and H2 production pathways, as the electrification of the chemical sector shows great potential for enormous greenhouse gas (GHG) emission mitigation despite the emerging challenges.